Pengaruh Media Educandy terhadap Hasil Belajar IPAS Siswa Kelas IV Sekolah Dasar - Diah Kusumaningsih; Rusni Eka Putra; Yuni Krisnawati (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2026)
This study aims to examine the role of Educandy as a digital learning medium in improving the learning achievement of fourth-grade students in Integrated Science and Social Studies (IPAS) at SD Negeri 59 Lubuk Linggau. This research employed a quantitative approach with a true experimental design. The research subjects consisted of all fourth-grade students who were divided into an experimental group using Educandy and a control group receiving conventional instruction. Data were collected through multiple-choice tests administered before and after the treatment. The instruments were tested for validity and reliability before use. The pretest results showed relatively similar initial abilities, with average scores of 41.17 for the experimental group and 42.11 for the control group. After the treatment, the experimental group achieved an average posttest score of 80.63, while the control group reached 69.68. Normality, homogeneity, and independent-samples t-tests were conducted to analyze the data. The results showed a statistically significant difference between the two groups, indicating that Educandy positively contributed to students’ learning achievement. Therefore, Educandy can be considered an effective digital learning medium to support interactive and engaging IPAS learning for fourth-grade elementary school students.